AC POWER CALIBRATION ON POWER QUALITY ANALYZER USING A MULTIPRODUCT CALIBRATOR - Hayati Amalia; Agah Faisal (Widyariset, 2017)
AC power calibration on power quality analyzer by using indirect method has been developed in Research Center for Metrology, Indonesian Institute of Science (LIPI). The measurement was performed by applying input voltage and input current from a standard multiproduct calibrator. Before being transferred to a power quality analyzer, the input current is passed first to the current coil to adapt the measuring range of the coil clamp of the power quality analyzer. Data collection and evaluation to determine the correction and uncertainty were carried out separately and alternately per phase. The analysis to evaluate the measurement correction and uncertainty was developed by considering the parameters that form the AC power, such as voltage, current, and phase angle. Based on the result of the calibration data analysis, it was obtained 5% of correction by the greatest measurement uncertainty of 1.92% at confidence level of 95% and coverage factor k=2.